PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DI BADAN USAHA MILIK DESA (BUMDES) - Iskamto, Dedi; Risman, Risman; Alwifari, Abuzar (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The objective of this research is to determine the effect of service quality on customer satisfaction in BUMDes Mitra Baru Desa Teratak kecamatan Rumbio Jaya. In analyzing the data generated from the research using descriptive and quantitative analysis using SPSS program. Based on the results In this research we get conclude that the quality of service Have a significant and positive influence To the customer satisfaction in BUMDes Mitra Baru Desa Teratak kecamatan Rumbio Jaya. From the regression results in this research , can be seen the regression equation as follows: Y = Y=10.679+ 0.745X. The meaning of regression equation above is: Constant value (a) velocity 10.679, meaning if independent variable that is service quality equal to zero, hence positive customer satisfaction 10.679. The value of regression reports of education and training variables of 0 .745, said increased increase in quality of service one unit meal customer satisfaction will increase by 0.745 units. Test Result t arithmetic (7.092)> t table (2.00856) and signifikasni (0,000) <0.05. Thus H0 is rejected and. What is meant by a significant influence on customer satisfaction on BUMDes Mitra Baru Desa Teratak kecamatan Rumbio Jaya.. The direction of its influence is positive. This means that the better the service quality will increase customer satisfaction BUMDes Mitra Baru Desa Teratak kecamatan Rumbio Jaya. The value of determination (R2) is 0.497. (Preferential relationship) to the dependent variable (satisfaction) of 49.7%. While the remaining 50.3% is not owned in this study